Step
*
2
2
of Lemma
eo-forward-le
1. eo : EO@i'
2. e : E@i
3. a : E@i
4. b : E@i
5. E ⊆r E
6. a = b ∈ E@i
⊢ a = b ∈ E
BY
{ (EqTypeCD⋅ THEN Folds ``es-base-E es-dom`` 0) }
1
1. eo : EO@i'
2. e : E@i
3. a : E@i
4. b : E@i
5. E ⊆r E
6. a = b ∈ E@i
⊢ a = b ∈ es-base-E(eo.e)
2
1. eo : EO@i'
2. e : E@i
3. a : E@i
4. b : E@i
5. E ⊆r E
6. a = b ∈ E@i
⊢ ↑(es-dom(eo.e) a)
3
1. eo : EO@i'
2. e : E@i
3. a : E@i
4. b : E@i
5. E ⊆r E
6. a = b ∈ E@i
7. e@0 : eo.e."E"
⊢ (↑(es-dom(eo.e) e@0)) = (↑(es-dom(eo.e) e@0)) ∈ Type
Latex:
1.  eo  :  EO@i'
2.  e  :  E@i
3.  a  :  E@i
4.  b  :  E@i
5.  E  \msubseteq{}r  E
6.  a  =  b@i
\mvdash{}  a  =  b
By
(EqTypeCD\mcdot{}  THEN  Folds  ``es-base-E  es-dom``  0)
Home
Index